2014
DOI: 10.1186/s13059-014-0548-2
|View full text |Cite
|
Sign up to set email alerts
|

Tomato nuclear proteome reveals the involvement of specific E2 ubiquitin-conjugating enzymes in fruit ripening

Abstract: BackgroundFruits are unique to flowering plants and play a central role in seed maturation and dispersal. Molecular dissection of fruit ripening has received considerable interest because of the biological and dietary significance of fruit. To better understand the regulatory mechanisms underlying fruit ripening, we report here the first comprehensive analysis of the nuclear proteome in tomato fruits.ResultsNuclear proteins were isolated from tomatoes in different stages of ripening, and subjected to iTRAQ (is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 76 publications
3
81
0
Order By: Relevance
“…The sonicated chromatin complexes were incubated with affinity purified polyclonal anti-SlVPE3/anti-RIN antibodies or pre-immune serum IgG (negative control) as previously described [28]. The cross-linking was then reversed, and the amount of each precipitated DNA fragment was determined by real-time PCR using specific primers (Additional file 8: Table S7).…”
Section: Methodsmentioning
confidence: 99%
“…The sonicated chromatin complexes were incubated with affinity purified polyclonal anti-SlVPE3/anti-RIN antibodies or pre-immune serum IgG (negative control) as previously described [28]. The cross-linking was then reversed, and the amount of each precipitated DNA fragment was determined by real-time PCR using specific primers (Additional file 8: Table S7).…”
Section: Methodsmentioning
confidence: 99%
“…One of the SNPs causing missense mutations was located at a putative ubiquitin-likespecific cysteine proteinase. Recent studies have shown the role of proteolysis in the regulation of fruit ripening in tomato (Wang et al, 2014(Wang et al, , 2017. Particularly, a vacuolar cysteine proteinase (SlVPE3) was shown to affect the accumulation of numerous ripening-related proteins, acting as a posttranscriptional regulator (Wang et al, 2017).…”
Section: Biological Insights Into the Genetic Basis Of Fruit-related mentioning
confidence: 99%
“…The mass spectrometry proteomics data have been deposited to the ProteomeXchange Consortium [95] via the PRIDE partner repository [96] with the dataset identifier PXD001414 [97].…”
Section: Data Accessmentioning
confidence: 99%